2018
DOI: 10.1016/j.dib.2018.08.170
|View full text |Cite
|
Sign up to set email alerts
|

Data on the alizarin red S adsorption from aqueous solutions on PAC, treated PAC, and PAC/γ≈Fe2O3

Abstract: Three types of adsorbents of powdered activated carbon (PAC), treated PAC, and PAC/γ ≈ Fe2O3 nanocomposite were used. The adsorption experiments were performed in batch conditions. pHZPC of PAC/γ ≈ Fe2O3 was 6.7. As a result, at lower than pHZPC, acidic pH, the adsorption of alizarin red S on PAC/γ ≈ Fe2O3 was favourable. The maximum of alizarin red S adsorption of PAC, treated PAC, and PAC/γ ≈ Fe2O3 was 24.5 mg/g, 57.8 mg/g, and 112.56 mg/g, respectively. The models of Langmuir and pseudo-first-order were a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…There are many different types of oxidation processes, each with its advantages and disadvantages. Single Ozonation Processes (SOP s ) is one of these processes which has been used in some studies (Kamarehie et al, 2018a;Kamarehie et al, 2018b;Schumacher et al, 2011). These processes, SOP s , have relatively low e ciency in removing contaminants and do not completely oxidize the contaminants (Asgari et al, 2015;Kamarehie et al, 2018a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are many different types of oxidation processes, each with its advantages and disadvantages. Single Ozonation Processes (SOP s ) is one of these processes which has been used in some studies (Kamarehie et al, 2018a;Kamarehie et al, 2018b;Schumacher et al, 2011). These processes, SOP s , have relatively low e ciency in removing contaminants and do not completely oxidize the contaminants (Asgari et al, 2015;Kamarehie et al, 2018a).…”
Section: Introductionmentioning
confidence: 99%
“…One of the most common compounds that can be used is activated carbon (GAC and PAC). Recently, the authors of this paper have reported that nanocomposite of MgO/PAC and PAC/γ-Fe 2 O 3 have high destructive adsorption, and high catalytic potential in the degradation of different pollutants including bisphenol A and Alizarene Red S (ARS) (Desalination-phenol;Kamarehie et al, 2018a;Kamarehie et al, 2018b;Kamarehie et al, 2018c). The environment is exposed to various pollutants daily, and the amount of pollution is increasing, day by day.…”
mentioning
confidence: 99%